Genomic Spectrum and Phenotypic Heterogeneity of Human IL-21 Receptor Deficiency - ÖZEN, AHMET OĞUZHAN; AYDINER, ELİF; BARIŞ, SAFA (SPRINGER/PLENUM PUBLISHERS, 2021)
Biallelic inactivating mutations in IL21R causes a combined immunodeficiency that is often complicated by cryptosporidium infections. While eight IL-21R-deficient patients have been reported previously, the natural course, immune characteristics of disease, and response to hematopoietic stem cell transplantation (HSCT) remain to be comprehensively examined. In our study, we have collected clinical histories of 13 patients with IL-21R deficiency from eight families across seven centers worldwide, including five novel patients identified by exome or NGS panel sequencing. Eight unique mutations in IL21R were identified in these patients, including two novel mutations. Median age at disease onset was 2.5 years (0.5-7 years). The main clinical manifestations were recurrent bacterial (84.6%), fungal (46.2%), and viral (38.5%) infections; cryptosporidiosis-associated cholangitis (46.2%); and asthma (23.1%). Inflammatory skin diseases (15.3%) and recurrent anaphylaxis (7.9%) constitute novel phenotypes of this combined immunodeficiency. Most patients exhibited hypogammaglobulinemia and reduced proportions of memory B cells, circulating T follicular helper cells, MAIT cells and terminally differentiated NK cells. However, IgE levels were elevated in 50% of IL-21R-deficient patients. Overall survival following HSCT (6 patients, mean follow-up 1.8 year) was 33.3%, with pre-existing organ damage constituting a negative prognostic factor. Mortality of non-transplanted patients (n = 7) was 57.1%. Our detailed analysis of the largest cohort of IL-21R-deficient patients to date provides in-depth clinical, immunological and immunophenotypic features of these patients, thereby establishing critical non-redundant functions of IL-21/IL-21R signaling in lymphocyte differentiation, humoral immunity and host defense against infection, and mechanisms of disease pathogenesis due to IL-21R deficiency. Outcome following HSCT depends on prior chronic infections and organ damage, which should thus be considered as early as possible following molecular diagnosis.
Keywords: IL-21; IL-21R signaling; T follicular helper cells; B cell differentiation; STAT3